The role graduate quantity surveyors in the Malaysian construction industry - B.L., Chong; W.P., Lee (2010)
The quantity surveying profession has evolved since changing of clients’ need and market requirements. Today, clients not only request the traditional services but also ask for the additional services such as project management, feasibility study, construction financial practice, arbitration, quality management, conflict management and risk management in the innovative and changing construction industry. The scope of works for graduate quantity surveyors is no longer limit on measurement and the regular practices but is some things beyond this boundary. Hence, the objective of this paper is to present a critical review on the traditional and contemporary roles of graduate quantity surveyors, the threats to graduate quantity surveyors and also the methods to improve graduate quantity surveyors’ practice. In summary, this critical review would provide insight knowledge to construction industry players for better understanding of graduate quantity surveyors’ roles.